Fractalkine promotes platelet activation and vascular dysfunction in congestive heart failure - Hildemann, Steven K.; Schulz, Christian; Fraccarollo, Daniela; Schöpp, Corinna; Flierl, Ulrike; Wissel, Kerstin; Pelisek, Jaroslav; Massberg, Steffen; Bauersachs, Johann; Schäfer, Andreas (Thrombosis and Haemostasis, 2014)
Endothelial dysfunction and enhanced platelet reactivity in congestive heart failure (CHF) contribute to poor prognosis. CHF patients display an impaired responsiveness to clopidogrel. Fractalkine activates platelets and elevated plasma levels of this chemokine are a feature of CHF. We here addressed the interrelation of fractalkine, platelet reactivity and clopidogrel efficacy in humans and rats with CHF. Fractalkine serum levels determined by ELISA were increased in CHF patients (CHF: 1548 ± 650 pg/ml; Control: 968 ± 575 pg/ml, p<0.01) and following CHF induction in rats (CHF: 1509 ± 753 pg/ ml; Sham: 1181 ± 275 pg/ml, p<0.05). Expression of fractalkine and its receptor CX3CR1 was enhanced in aortas of CHF rats as determined by immunofluorescence microscopy and molecular analysis. Fractalkine significantly aggravated endothelial dysfunction and augmented P-selectin expression on platelets from CHF rats. Platelet surface expression of CX3CR1 was increased in CHF rats, who displayed an impaired response to clopidogrel (platelet reactivity to ADP: CHF 30 ± 22%; Sham: 8 ± 5%, p<0.05). Similarly in humans with CHF, elevated fractalkine levels were accompanied by reduced clopidogrel responsiveness. Patients with high on-clopidogrel treatment platelet P2Y12 reactivity displayed higher fractalkine levels (1525 ± 487 pg/ml) than those with sufficient clopidogrel response (684 ± 315 pg/ml, p<0.01). In conclusion, in CHF fractalkine was increased on the endothelium and in blood serum, and platelet surface- expression of CX3CR1 was enhanced. Fractalkine diminished endothelial function beyond the impairment already observed in CHF and was associated with a reduced responsiveness to the platelet inhibitor clopidogrel. These findings may indicate a novel pathophysiological mechanism contributing to impaired clopidogrel responsiveness in CHF.
Keywords: Fractalkine; chemokines; heart failure; platelets; endothelial dysfunction; clopidogrel